Necesidad de reformar el art. 38 del código orgánico integral penal, a fin de sancionar penalmente a los adolescentes infractores que cometen delitos contra inviolabilidad de la vida - Castillo Briceño, José Luis (2015)
Juvenile delinquency is as old as mankind. Despite not having any doubt about the existence of a pre-Columbian criminal law, such as the Aztec peoples, Mayas, Incas or Mesoamerica know if there was any particular or specific regulation for children and youth who commit a "crime ". As well as the regulations of these conditions are unknown in the so-called American colonial law. "In the late nineteenth century most Latin American countries had a sufficient coding, especially in political constitutions and penal codes, regulation of juvenile crime was not given special attention". It is at the beginning of this century when the concern for children is located in 105 countries of our region. This is the result of the internalization of ideas that start in the twentieth century, first with the Positive School and then the School of Social Defense. "The first specific legislation was Argentina is known, was enacted in 1919. But in later decades in which most of the first laws were enacted. This led to special rules in the juvenile criminal law , both substantive scope and formal, such as pre-criminal behavior, irregular and indeterminate sentence . " A milestone in the historical development of the right of children marked the Promulgation of the General Convention of Children's Rights in 1989, after the entry into force of this convention has been started in the 90's a process of reforms and legislative adjustments in several countries in the region , specifically in Colombia , Brazil, Ecuador , Bolivia , Peru , Mexico and Costa Rica " . Crime has increased alarmingly in recent times , becoming increasingly a problem that generates greater social concern , both for its quantitative increase , and its progressive qualitative danger is so : • On the morning of May 25, 2011, the body of Damaris Cabrera, 16, was found in jute bags in the gorge of Santa Barbara in Chillogallo (south of Quito), in the abduction, torture and murder of Damaris They involved two minors. • In 2010, a 16 year old girl was beheaded in Machala (El Oro). Another minor was involved in the incident and was sentenced to four years' imprisonment. Even our current President Eco. Rafael Correa said that "serious crimes committed by minors should be proportional to that of adults and sanctions should be cumulative. The critical factor is to believe that age is a decisive factor for establishing penalties "he said. Crimes committed by minors are increasing, therefore, there must be criminal intervention as to eradicate this kind of violations and protect people that the sanction is commensurate with the gravity of the offense is required ( which takes into account the circumstances of the offense) regardless of age.